Spillovers of Domestic Shocks : Will They Counteract the 'Great Moderation'? - Mody, Ashoka (IMF Working Papers; Working Paper ;, 2010)
Even prior to the extreme volatility just observed, output growth volatility-following protracted decline-was flattening or mildly rising in some countries. More widespread was an increasing tendency from the mid-1990s for shocks in one country to transmit rapidly to other countries, creating the potential for heightened global volatility. The higher sensitivity to foreign shocks, in turn, appears related to stepped-up vertical specialization associated with the integration of emerging markets in international trade. Increased international spillovers call for stronger ex post coordination mechanisms when shocks are large but the best ex ante prevention strategy probably is sensible national policies.